THE RELATIONSHIP BETWEEN COFFEE CONSUMPTION AND SLEEP QUALITY WITH THE INCIDENCE OF ACNE VULGARIS - Maulana Achmad; Popi Sopiah; Rafika Rosyida (Buletin Veteriner Udayana, 2024)
Acne vulgaris, or acne, was a common skin problem that occurred in adolescents and young adults, and had a significant psychological impact, especially on individual self-confidence. The high prevalence of this issue, along with factors such as dietary patterns, sleep habits, and coffee consumption, led to a need for deeper understanding of its relationship with skin conditions. This study aimed to evaluate the association between coffee consumption and sleep quality with the occurrence of acne vulgaris. The research method used a quantitative approach with a survey design and descriptive correlational method in a cross-sectional research approach. The instruments included a coffee consumption questionnaire with a Cronbach’s alpha value of 0.707 and a PSQI (Pittsburgh Sleep Quality Index) questionnaire with a Cronbach’s alpha value of 0.888. The study sample consisted of students from Universitas Pendidikan Indonesia Kampus Sumedang who experienced acne problems, frequently consumed coffee, and had insufficient sleep hours. Data collection was conducted through questionnaires that covered information about coffee consumption patterns and types of coffee consumed, as well as sleep patterns. The research results indicated that there was no significant relationship between coffee consumption and the occurrence of acne vulgaris, with a p-value of 0.106 (>0.05). However, there was a significant association between sleep quality and the occurrence of acne vulgaris, with a p-value less than 0.001. The conclusion from this study was that coffee did not directly impact the growth of acne, but poor sleep quality could directly affect acne occurrence. Further research is expected to explore other factors that may cause acne vulgaris.